Lipid abnormalities in patient with chronic kidney disease: a cross sectional study - Giri, Rajendra Mani; Gorkhaly, Manen Prasad (Journal of Karnali Academy of Health Sciences, 2022)
Introduction: Chronic Kidney disease (CKD) is a public health problem with an increasing incidence and prevalence, poor outcomes, and high cost. Renal disease, in early as well as advanced stages, is associated with abnormalities in lipoprotein metabolism. Dyslipidemia appears to be independently associated with increased progression rate of CKD in patients with kidney disease and with increased risk of graft loss after renal transplantation. This study was conducted to study the lipid abnormalities in CKD patients. Methodology: A hospital-based, observational, cross-sectional study was conducted among 89 patients admitted in the ward of Bir Hospital with the diagnosis of CKD. Data was collected using the structured pro-forma. Data was analyzed using SPSS version 16. Descriptive statistics (Frequency, mean and percentage) was used. Results: In this study the average value of total cholesterol (TC), triglyceride, low density lipoprotein (LDL) and high-density lipoprotein (HDL) were 246.66±53.56, 215.78±80.70, 168.61±44.73, 35.77±5.26 respectively. In this study there is significant association between HDL, LDL, triglyceride (TG) & total cholesterol with smoking with p value of 0.001, 0.003, 0.001& 0.003048 respectively. Similarly there is also significant relationship between HDL, LDL, TG& total cholesterol with age with p value of 0.001, 0.048, 0.010 & 0.048 respectively. Conclusion: Hypertriglyceridemia and low HDL and LDL are the common lipid abnormalities in CKD patients.